Analisis Indeks Keterampilan Bermain Bolavoli Siswa Ekstrakurikuler Bola Voli SMP Negeri 1 Maniangpajo Kecamatan Maniangpajo Kabupaten Wajo - Andi Rizal; Adam Mappaompo; Akbar Sudirman; Muhammadong (Jurnal Multidisiplin Madani, 2022)
Analysis of the Volleyball Skills Index for Volleyball Extracurricular Students at SMP Negeri 1 Maniangpajo, Maniangpajo District, Wajo Regency. Research on the volleyball skill index of students participating in volleyball extracurricular activities at SMP Negeri 1 Maniangpajo, Wajo Regency, aims to find out how good the volleyball skill index is. with a survey method on all students participating in volleyball extracurricular activities, with a sample of 20 people. Using a volleyball skill test instrument Age 13-15 Years Center for Physical Refreshment and Recreation of the Ministry of National Education in 1999. These include: Passing down, Passing up, serving down, serving up, and Smash. Furthermore, data analysis using descriptive statistics are percentages. The result is the volleyball skill index of the volleyball extracurricular students of SMP Negeri 1 Maniangpajo, Maniangpajo District, Wajo Regency. "Medium" category with the highest frequency of 13 (65%).